Antennal morphology and sensilla ultrastructure of Ascia monuste (Linnaeus) (Lepidoptera: Pieridae). (March 2021) - Limberger, Guilherme Martins; Brugnera, Ricardo; Fonseca, Duane Barros da
Highlights: Antennal morphology and ultramorphology have been described for Ascia monuste . Sensilla trichodea, chaetica, basiconica and coeloconica have been found. Antennal length is sexually dimorphic, but the types of sensilla are not. Results have been discussed comparatively among the Pieridae. Abstract: Insects have different types of cuticular sensory structures, called sensilla, which are employed in environmental perception due to their direct connection to the nervous system. Antennae are the main structures containing these sensilla in Lepidoptera. This study used scanning electron microscopy to describe the general morphology and the types of antennal sensilla of the great southern white butterfly, Ascia monuste, an important pest that feeds on cruciferous plants during its larval stages. Organizational, distributional, and functional aspects are comparatively discussed, as well as potential sexual dimorphism. Sensilla and general morphology were analyzed using a stereomicroscope and photomicrographs in the ImageJ software. Four types of sensilla were found in males and females: sensilla trichodea, chaetica, basiconica and coeloconica. The number of flagellomeres was different between sexes, with females having more articles and a longer antennal length than males. The capitate antenna of this butterfly had a unique elliptical central sulcus in the median ventral surface of each segment, mostly containing sensilla trichodea. Some organizational aspects of the sensilla chaetica close to the central sulci along the flagellum were observed. The remaining sensilla were randomly distributed on the antenna, mainly at the ventral surface, while the dorsal surface was almost totally covered by scales. This is the first report about ultrastructural morphology of the antenna of A. monuste, whose sensilla appear similar to those of other Pieridae butterflies, suggesting mechanical, chemo-, thermo-, and hygro-sensitivity in this insect.